Serum iron and transferrin in acute neuroleptic induced akathisia. - O'Loughlin, V; Dickie, A; Ebmeier, K (1991)
Thirty acute psychiatric patients were examined prospectively at the beginning of neuroleptic treatment for acute psychotic symptoms and on average 16 days later. Two alternative hypotheses were examined: 1) neuroleptic treatment affects the levels of serum iron and transferrin; 2) acute akathisia developing during the initial few weeks of treatment is associated with low levels of serum iron and transferrin, either initially or at follow up or both. Serum iron levels did not change on repeat measurement, while there was a small, but significant decrease of serum transferrin. There was a significantly greater decrease in iron and transferrin levels in patients with akathisia on follow up compared with non-akathisics. In addition, akathisia ratings were highly correlated with serum transferrin levels on follow up.